Validation of a Research Instrument for Safety Leadership and Safety Knowledge-Attitude-Behaviour (KAB) for Malaysia Manufacturing Set-Up - SYAZWAN SYAH ZULKIFLY; Mohd Rafee Baharudin; Muhammad Razif Mahadi; Sharifah Norkhadijah Syed Ismail; Nor Halim Hasan (iRASD Journal of Management, 2021)
This article provide an empirical evidence  on the validity of a questionnaire designed to assess safety leadership, as well as safety knowledge-attitude-behaviour (Safety KAB) within Malaysia’s manufacturers which fall under small and medium (S & M) entrepreneurship. The questionnaire’s items were adapted from earlier research conducted in other study contexts. First, modified fuzzy delphi method (FDM) was applied for the research to obtain expert’s consensus regarding the content validity of all items. With some modifications to suit Malaysia’s SME manufacturing setting, the  5 point Likert-scale questionnaire consisting 42 items for measuring safety leadership and safety KAB were finalised. Subsequently, it was distributed to 100 production operators from the manufacturing S& M enterrpises in the Northern Corridor Economic Region (NCER) of Malaysia for pilot testing, 95 respondents had answered. They returned the questionnaires and 89 were best to be chosen for further procedures.The determined Cronbach’s alpha values were more than 0.90 for all items representing those variables, indicating that the questionnaire possessed high reliability and internal consistency. Subsequently, exploratory factor analysis (EFA) employing principal component analysis (PCA) extraction and varimax rotation was performed to determine the construct validity.  According to the PCA results, each item was retained as all the factor loadings were above the decided cut-off value, which is 0.65. Henceforth, the questionnaire is considered valid and reliabile to be used by future researchers.